Factors associated with severity in invasive community-acquired Staphylococcus aureus infections in children: a prospective European multicentre study. (July 2016) - Gijón, M.; Bellusci, M.; Petraitiene, B.; Noguera-Julian, A.; Zilinskaite, V.; Sanchez Moreno, P.; Saavedra-Lozano, J.; Glikman, D.; Daskalaki, M.; Kaiser-Labusch, P.; Falup-Pecurariu, O.; Montagnani, C.; et al.
Abstract: Staphylococcus aureus is the main pathogen responsible for bone and joint infections worldwide and is also capable of causing pneumonia and other invasive severe diseases. Panton-Valentine leukocidin (PVL) and methicillin-resistant S. aureus (MRSA) have been studied as factors related with severity in these infections. The aims of this study were to describe invasive community-acquired S. aureus (CA-SA) infections and to analyse factors related to severity of disease. Paediatric patients (aged 0–16 years) who had a CA-SA invasive infection were prospectively recruited from 13 centres in 7 European countries. Demographic, clinical and microbiological data were collected. Severe infection was defined as invasive infection leading to death or admission to intensive care due to haemodynamic instability or respiratory failure. A total of 152 children (88 boys) were included. The median age was 7.2 years (interquartile range, 1.3–11.9). Twenty-six (17%) of the 152 patients had a severe infection, including 3 deaths (2%). Prevalence of PVL-positive CA-SA infections was 18.6%, and 7.8% of the isolates were MRSA. The multivariate analysis identified pneumonia (adjusted odds ratio (aOR) 13.39 (95% confidence interval (CI) 4.11–43.56); p 0.008), leukopenia at admission (<3000/mm 3 ) (aOR 18.3 (95% CI 1.3–259.9); p 0.03) and PVL-positive infections (aOR 4.69 (95% CI 1.39–15.81); p 0.01) as the only factors independently associated with severe outcome. There were no differences in MRSA prevalence between severe and nonsevere cases (aOR 4.30 (95% CI 0.68– 28.95); p 0.13). Our results show that in European children, PVL is associated with more severe infections, regardless of methicillin resistance.